2015
DOI: 10.1038/srep12107
|View full text |Cite
|
Sign up to set email alerts
|

Differential patterns of blood oxygenation in the prefrontal cortex between patients with methamphetamine-induced psychosis and schizophrenia

Abstract: Despite some slight differences in symptomatology, differential diagnosis of methamphetamine-induced psychosis (MAP) versus schizophrenia can be challenging because both disorders present a large overlap in their clinical symptoms. However, a recent study has shown that near-infrared spectroscopy (NIRS) performed during a cognitive task can be a powerful tool to differentiate between these two disorders. Here, we evaluated verbal fluency task performance during NIRS in 15 patients diagnosed with MAP and 19 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…In a small study of 11 patients with chronic METH psychosis who had been abstinent from METH for more than 1 month ( 114 ) qualitatively reported that five subjects experienced visual hallucinations, seven experienced delusions of reference and persecutory delusions while all experienced auditory hallucinations. Additionally, Yamamuro et al ( 116 ) found similar PANSS results in their experimental study examining oxygenation changes in the prefrontal cortex in acute METH psychosis and schizophrenia during a verbal fluency task. Furthermore, Wang et al ( 115 ) examined the positive symptom profile of 52 individuals with chronic METH psychosis (who experienced psychosis and had been abstinent from METH for more than 1 month) and compared this to 53 participants with schizophrenia.…”
Section: Positive Symptomsmentioning
confidence: 66%
“…In a small study of 11 patients with chronic METH psychosis who had been abstinent from METH for more than 1 month ( 114 ) qualitatively reported that five subjects experienced visual hallucinations, seven experienced delusions of reference and persecutory delusions while all experienced auditory hallucinations. Additionally, Yamamuro et al ( 116 ) found similar PANSS results in their experimental study examining oxygenation changes in the prefrontal cortex in acute METH psychosis and schizophrenia during a verbal fluency task. Furthermore, Wang et al ( 115 ) examined the positive symptom profile of 52 individuals with chronic METH psychosis (who experienced psychosis and had been abstinent from METH for more than 1 month) and compared this to 53 participants with schizophrenia.…”
Section: Positive Symptomsmentioning
confidence: 66%
“…A study using inhibition tasks found great similarities in the ventrolateral prefrontal cortex, suggesting similarities in the underlying pathophysiology of psychosis induced by amphetamines and by schizophrenia [22]. However, both this and another study found that, despite great similarities, there are also subtle differences in the prefrontal cortex [23]. Those with methamphetamine-induced psychosis show a similar age of onset of methamphetamine use and the same frequency of current substance use as those with primary psychosis [24 & ], but the former have fewer hospital admissions and lower use of antipsychotics despite similar severity of psychotic symptoms.…”
Section: Complex Relationship Between Primary Psychosis and Amphetamimentioning
confidence: 56%
“…CNS stimulants, such as modafinil, may only increase dopamine in the prefrontal cortex. The brain target site influenced by CNS stimulant is different from that for pathophysiology of schizophrenia may count for the possible mechanism that CNS stimulants not seem to enhance psychosis (63,64).…”
Section: Pharmacotherapy and Psychotic Disorder In Narcoleptic Patientsmentioning
confidence: 99%